Inclusive development policy research: research identification, and future agenda - Ida Widianingsih; Abdillah Abdillah; Qinthara Mubarak Adikancana (Cogent Social Sciences)
This systematic literature review aims to identify, review, and study the development of trends in scientific publications regarding inclusive development and policies in overcoming development problems concerning a lack of widespread prosperity that is developing in the world. Our aim is to map recent research and publication activities of authors to identify growing evidence concerning the problem of inclusive development in various regions and how policies support inclusive development. This research provides scientific guidelines and recommendations to develop studies on how policies support inclusive development in various regions. This research can be used as scientific data and policy notes on the issue of inclusive development in encouraging social, economic, and environmental/ecological growth in regional development. The findings of this study evaluate the taxonomy of the literature review through three specific analyses: (1) time analysis, to explore the causes of inclusive development literature trends and policies in dealing with development problems in the last 10 years; (2) terminology analysis, to examine how and where the two failures are related and influence each other; and (3) typology analysis, to investigate whether the ‘Inclusive Development & Policy’ has a positive effect on addressing issues of human development (discrimination), economy, education, equitable development, accessibility, and the environment.